The battle for Perodia - Charman, Katrina; Tondora, Judit (New York, NY : Branches/Scholastic Inc., 2019)
"It is finally time to fight for the enchanted land of Perodia! Tag, Skyla, and Blaze call on their friends to help them in the epic battle against Thorn. Blaze will have to learn how to use the magical Ember Stone. But will its bright magic be strong enough to defeat the powerful vulture and his dark army of spies?"--Page [4] of cover.
Reading level grade 2
1st-3rd graders.
590L
Decoding demand: 73 (high) Semantic demand: 95 (very high) Syntactic demand: 71 (high) Structure demand: 85 (very high)
Keywords: Owls -- Juvenile fiction; Squirrels -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Magic -- Juvenile fiction; Good and evil -- Juvenile fiction; Imaginary wars and battles -- Juvenile fiction; Fantasy fiction; Animal fiction; Action and adventure fiction